Developing Picture in the Box Media for Understanding Traditional Riau Traditional Food in Class IV Elementary Schools - Qurrota Akyuni Azzahra; Zariul Antosa; Eddy Noviana (CV. Rayyan Dwi Bharata, 2024)
This research aims to produce a product for the development of learning media for the introduction of traditional Riau food in Class IV Elementary School, which carried out feasibility and practicality tests on the media. The research method used in this research is the Research and Development (RD) development method with the ADDIE model. The ADDIE model development stage consists of the Analysis, Design, Development, Implementation and Evaluation stages. The media developed by researchers has been validated by 2 experts, consisting of a media expert and a material expert. Then, to test the practicality of the media, it can be seen from the response questionnaire from students and class teachers which was carried out in large group trials. The data collection techniques used by researchers consist of interviews, observations and questionnaires. Based on the results of media validation, the percentage obtained was 81.82% in the very suitable category for media expert validation, and 98.44% in the very suitable category for material validation. Then a small group trial was carried out reaching a percentage of 88.75% in the very practical category and a large group trial reached a percentage of 91.98% in the very practical category. Meanwhile, the percentage of teacher responses reached 93.75% in the very practical category.